The Effect of Audit Quality on the Audit Adjustments to Earnings - Seyed Reza Seyed Nezhad Fahim; Samaneh Zamani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This paper aims to investigate the role and impact of audited quality indicators on the amount of audited earnings corrections. Methodology: Three indicators, auditor tenure, auditor size, and auditor fees, were used to measure the audit quality. Research hypotheses based on collected data from 128 companies accepted in the Tehran Stock Exchange from 2013 to 2018 were tested using combined regression analysis. Findings: The test results showed a significant positive relationship between auditor tenure and auditor industry specialization with audit adjustments to earnings, but there is a negative and meaningless relationship between auditor fees, auditor size, and auditor rate with audit adjustments to earnings. To further analyze, the effect of audit quality on the downward audit adjustments to earnings was also examined. Evidence indicates a significant positive relationship between auditor tenure and auditor industry specialization with downward audit adjustments to earnings and a significant negative relationship between auditor size and auditor rate with downward audit adjustments to earnings. Originality/Value: In this research, five indicators of auditor tenure, auditor size, auditor rank, auditor specialization in industry, and auditor fee were used as criteria for audit quality.